Quality Evaluation of Indigenous Taro (Colocasia esculenta L.) Cultivars of Nagaland - BURAGOHAIN, JURI; ANGAMI, T.; CHOUDHARY, B. U.; SINGH, P.; BHATT, B. P.; THIRUGNANAVEL, A; DEKA, BIDYUT C. (Indian Journal of Hill Farming, 2014)
Twenty locally grown taro (Colocasia esculenta L. Schott.) cultivars were collected from different parts of Nagaland, and their morphological and chemical analysis were done. The different parameters analyzed include corm length, corm diameter, specific gravity, number of cormels, starch, calcium oxalate, moisture, dry matter, energy, nitrogen (N), phosphorous (P), potassium (K), calcium (Ca), magnesium (Mg) and sulphur (S) contents. Wide variability in nutritional and other quality parameters like starch, calcium oxalate, dry matter etc. among the different taro cultivars was recorded. There was strong positive correlation (P < 0.05) between corm length and specific gravity; calcium oxalate and moisture content. Among the 20 cultivars, Nalon, Toongphak, Tanchong Shg, Angphak and Toa Boi were found superior to others with respect to yield attributes, nutritional and other quality parameters based on an over-all rank sum index (ORSI).